The Teflon effect: when the glass slipper meets merit. Issue 8 (1st November 2016) - Simpson, Ruth; Kumra, Savita
Abstract : Purpose: This paper aims to draw on Ashcraft's (2013) metaphor of the "glass slipper" (which highlights the need for alignment between occupational identity and embodied social identities of workers) to show how merit may not adhere to individuals when social identity in the form of gender, race or class fails to fit the definition and perceived characteristics of the job. Design/methodology/approach: This is a conceptual paper. Findings: This study develops the notion of the Teflon effect to describe the way merit may go unrecognised and may therefore not "stick" to the bodies of women in management and leadership roles. Research limitations/implications: This study provides an explanation for the persistence of the glass ceiling and the barriers women face as they undertake or aspire to management and/or leadership positions in organisations. Practical implications: This study introduces a more embodied notion of merit which relies on both performance and recognition to "take effect". Professionals must see beyond "objective" measures of merit in performance reviews and/or in recruitment and promotion decisions to include reflection on the significance of merit's subjective, "performed" dimensions. Social implications: This study adds to understandings of women's positioning in organisations. Originality/value: This study develops the notion of the Teflon effect. This highlights the significance of the recognition, performance and embodiment of merit and how merit may fail to adhere to the bodies of women in management and leadership roles.